Tantangan Pondok Pesantren Menuju Lembaga Pendidikan Islam yang Akuntabel - Ahyar, Muhammad Khozin (JIFA (Journal of Islamic Finance and Accounting), 2020)
Islamic boarding school is one of the oldest Islamic education institutions in Indonesia. The majority of Islamic boarding schools in Indonesia are foundations. As an institution or non-profit entity, Islamic boarding schools also need to do an institutional transformation so that it can continue to grow and be trusted by stakeholders. So far, the financial reporting of Islamic boarding schools does not have standardization. So that each boarding school has a different form of financial reporting. In the end, Bank Indonesia and the Indonesian Institute of Accountants (IAI) developed the Pesantren Accounting Guidelines (PAP). Pesantren Accounting Guidelines are one of the programs in the development of pesantren economic independence. This article aims to describe the challenges faced by Islamic boarding schools in achieving accountable Islamic education institutions. Based on the literature review, there are three challenges in Islamic boarding schools in order to become an accountable Islamic educational institution, namely the boarding school human resources in the field of accounting, cooperation between related institutions and the use of technology. Islamic boarding schools must increase or increase competent human resources in the fields of accounting and financial reporting. Collaboration between related institutions can help boarding schools in increasing accountability. The provision of technology and the procurement of a type of software or application can make it easier for Islamic boarding school human resources to prepare financial reports in accordance with financial accounting standards (SAK), in this case in accordance with Islamic Boarding School Accounting Guidelines.Keywords: Islamic Boarding School, Accountable, Islamic Boarding School AccountingJEL Classification Codes: L31, Z12, Z18